Biological activity of 4-amino-5-methyl-4h-1,2,4-triazol-3-thione derivatives - Kravchenko, T. V.; Кравченко, Тетяна Вікторівна (Львів: ГО "Львівська медична спільнота", 2018)
One of the main tasks of pharmaceutical chemistry with regard to 1,2,4-triazole derivatives is finding new highly effective, less toxic, and, consequently, with mild-to-none side effects biologically active compounds. The derivatives of 1,2,4-triazole are ones of the most important synthetic medicinal products [1]. Nowadays, drugs containing 1,2,4-triazole structure, such as fluconazole, ribavirin, trizadone, trifuzol and many other, are widely used in medical practice [2].
Keywords: тези